Literature Review on The Comparing Usability of Through Flow Filtration and Tangential Flow Filtration - Sapitri, Putu Dian; Pranatha, I Putu Adhi; Kartini, Ni Komang Triayu Cita; Erlina, Ni Putu Natasha Ernianti; Pangestu, Ade Winanda; Putra, I Gusti Ngurah Agung Dewantara (PC Ikatan Apoteker Indonesia (IAI) Karanganyar, 2024)
Sterilization is a process of removing, killing, or destroying all living microorganism, both pathogenic and non-pathogenic, including spore or vegetative forms, from an object or materials. The choice of sterilization method depends on the properties of the material to be sterilized, such as resistance to heat and the shape of the media. The membrane filtration method can be done in two ways, namely Through Flow Filtration (Normal Flow Filtration) and Tangential Flow Filtration. Normal flow filtration (Normal Flow Filtration) or also known as flow-through filtration (Through Flow Filtration) is a process of separating solid particles from a liquid that utilizes constantly applied hydrostatic pressure. The aim of this literature study is to summarize several articles from international journals and national journals obtained from several sources database on the Internet, like Google Scholar, Science Direct, Researchgate, Pubmed, and Springerlink. Articles that meet the inclusion criteria are then analyzed and described. From the results of library searches that have been carried out on the Google Scholar site online The number of libraries obtained was (n=131). The literature selection was carried out by screening the title and abstract so that the remaining number was (n=78). The library used in its entirety on review this article totals (n=34).